Visualiseringsstrategier og erindringsarkitektur i Snorri Sturlusons Edda - Pernille Hermann (Religionsvidenskabeligt Tidsskrift, 2022)
ABSTRACT: This article investigates Snorri Sturluson’s Edda seen in light of medieval memory theory. It is argued that the pagan myths that are treated in bookish culture are adjusted to ideas about memory that circulated in the 13th century. It is shown that important mnemonic principles, such as spatiality and visuality, have put their stamp on the Edda and other mythological texts, which seem to describe and transmit to their readers comprehensive memory architectures and topographies. The mnemonic dimensions of the texts are important to include in source critical discussions, when the medieval texts are used as sources to pre-Christian mythology.